2013
DOI: 10.1177/1059601112472726
|View full text |Cite|
|
Sign up to set email alerts
|

Unraveling the Relationship Between Family-Supportive Supervisor and Employee Performance

Abstract: This study examined the role of job satisfaction, relational identification with supervisor, and work-family conflict in explaining the influence of familyfriendly supervision (FFS) on supervisor-rated citizenship behavior and task performance using data from a Chinese pharmaceutical company. Hierarchical regression analysis results revealed that job satisfaction mediated the relationship between FFS and supervisor-rated citizenship behavior, whereas relational identification with supervisor mediated the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 95 publications
1
42
0
Order By: Relevance
“…Of the behaviors researched in the literature, performance was the most commonly studied, being found in nine articles. , affective commitment , job self-efficacy , WTFE (Odle-Dusseau et al, 2012), engagement (Rofcanin, Las Heras, & Bakker, 2016), job satisfaction (Wang et al, 2013), and relational identification with supervisor (Wang et al, 2013). Bagger and Li (2014) found support for a moderated mediation, whereby family-friendly benefits moderated the indirect effect of FSSB on both task performance and OCB towards the supervisor through social exchange with supervisor.…”
Section: Job Behavior Outcomesmentioning
confidence: 99%
“…Of the behaviors researched in the literature, performance was the most commonly studied, being found in nine articles. , affective commitment , job self-efficacy , WTFE (Odle-Dusseau et al, 2012), engagement (Rofcanin, Las Heras, & Bakker, 2016), job satisfaction (Wang et al, 2013), and relational identification with supervisor (Wang et al, 2013). Bagger and Li (2014) found support for a moderated mediation, whereby family-friendly benefits moderated the indirect effect of FSSB on both task performance and OCB towards the supervisor through social exchange with supervisor.…”
Section: Job Behavior Outcomesmentioning
confidence: 99%
“…Scholars also suggested that is important to control for tenure with the supervisor knowing that possible temporal effects might explain the influence of the relationship with the supervisor on outcomes (e.g. Wang et al, 2013). Finally, prior research indicated that woman generally report higher levels of stress (e.g.…”
Section: Test Of Hypothesesmentioning
confidence: 99%
“…At the same time, although many organizational scholars have recognized that PI is important, they have disagreed on whether its impact is helpful or harmful. For instance, whereas some research indicates that identifying with one's leader is associated with higher job satisfaction and individual performance (Hobman, Jackson, Jimmieson, & Martin, 2011;Wang, Walumbwa, Wang, & Aryee, 2013;Wang & Howell, 2012), other research indicates that this is associated with dependence on the leader and unethical behavior (Gino & Galinsky, 2012;Kark, Shamir, & Chen, 2003). Additionally, the mentoring literature offers many positive consequences associated with a close mentoring relationship involving identification processes, including internalization of desired attributes, career development, and psychosocial support (Bouquillon, Sosik, & Lee, 2005;Kram, 1985;Ragins, 1997a;Ragins & Cotton, 1999;cf.…”
mentioning
confidence: 99%